Preparing clinicians for (re-)emerging arbovirus infectious diseases in Europe. (March 2018) - Sigfrid, L.; Reusken, C.; Eckerle, I.; Nussenblatt, V.; Lipworth, S.; Messina, J.; Kraemer, M.; Ergonul, O.; Papa, A.; Koopmans, M.; Horby, P.
Abstract: Background: Arthropod-borne virus (Arbovirus) infections are considered an emerging threat for Europe, with an increase in cases in recent decades. The increase in global travel and trade has contributed to the introduction of vectors and viruses into new geographical areas. Tropical arboviruses such as dengue and chikungunya have re-emerged causing local, sporadic outbreaks ignited by travel-imported cases. The recent Zika virus outbreak in the Americas highlighted a need to strengthen preparedness for (re-)emerging arbovirus infections globally. Aims: To strengthen preparedness for the early identification of (re-)emerging arbovirus outbreaks in Europe and highlight areas for research. Sources: An evidence review of published and grey literature together with consultations with European arbovirus experts. Content: This paper presents an overview of endemic and travel-imported arboviruses of clinical significance in Europe. The overview includes syndromic presentation, risk factors for infection and risk of transmission as well as an update on treatments and vaccinations and surveillance notifications and reporting. The paper also presents predictive modelled risks of further geographical expansion of vectors and viruses. Implications: There are a range of arboviruses of clinical significance to Europe. There has been an increase in notifications of endemic and travel-imported arbovirus cases in recent years and an increased geographical range of vectors and viruses. The heterogeneity in surveillance reporting indicates a risk for the early identification of (re-)emerging outbreaks. The data presented show a need to strengthen preparedness for (re-)emerging arbovirus infections and a need for research into neglected arboviruses, risks of non-vector transmission and effective therapeutics and vaccinations.